Accuracy of NADAS criteria to establish diagnosis in children with suspected congenital heart disease - Rahmawati Rahmawati; Rizky Adriansyah; Yunnie Trisnawati; Juliandi Harahap; Pertin Sianturi; Ayodhia Pitaloka Pasaribu (Paediatrica Indonesiana, 2023)
Background The majority of congenital heart disease is diagnosed during evaluation of a murmur detected either during a routine follow-up or while assessing an intercurrent illness. NADAS criteria might be useful as a screening test to differentiate pathologic from innocent murmurs. Objective To assess the accuracy of NADAS criteria in diagnosing pathology in children with suspected congenital heart disease. Methods This diagnostic study included children aged 1 month - 12 years who visited the Outpatient Pediatric Cardiology Clinic at Haji Adam Malik General Hospital, Medan, North Sumatera. Inclusion criteria from history and physical examination were recurrent acute respiratory illness (ARI), poor nutritional status, failure to thrive, cardiac murmurs, and/or a history of cyanosis. Results Seventy children underwent NADAS screening, of whom 60 had CHD. In the <5-year age group, 63.3% had heart disease. All patients had poor nutritional status, both CHD and non-CHD patients. All CHD patients had an abnormal electrocardiogram (ECG), while 88.33% had a history of recurrent ARI, 80% had abnormal chest x-ray, and 55% had abnormal S2 heart sound on auscultation. A grade 3 or higher systolic murmur was found in 78.33% of patients who had CHD. There were 55 children who had a NADAS score of 3 or higher, of which 53 children with CHD and 2 children non CHD (1 of the 2 children non CHD showed only 3 minor criteria of the NADAS score and had infantile fibrosarcoma). The other 15 children had a NADAS score of less than 3 with 7 children with CHD and 8 children without CHD. Conclusion The NADAS criteria can be used as a screening test to diagnose disease in children suspected of having CHD for cut-off score at 3 (1 major + 2 minor), with 87.14% accuracy, 88.33% sensitivity, 80% specificity, and 0.883 AUC value.